Multimodal Analysis Of Coffee Shop Franchises In Medan City - Monika Sales Sitompul; Thyrhaya Zein; Masdiana Lubis (International Journal of Educational Research & Social Sciences, 2021)
This paper discusses a multimodal analysis of 10 (ten) coffee outlets that has been determined in the city of Medan, namely Starbucks, Kopi Orang Dalam, Kopikuni, Suara Coffee, Daily Dose Coffee, Kopi Kenangan, Kopi Cantik Jiwa, Filosopi Kopi, Hidden Place, and Blanco. Coffee. The purpose of this study was to find the meaning conveyed through writings, and the symbolic meaning conveyed through images, logos, or other decorations contained in the coffee shop to the viewer. This research uses Kress and Van Leuween's visual metafunction theory. The data in this study are visual data in the form of logos, name planks, pictures, paintings or other decorations found in the coffee shop. The method used in this research is descriptive qualitative by using the method of observation, study documentation and interviews, while the data analysis technique uses an interactive model by Miles, Huberman & Saldana. The results showed that the interactive meaning contained in the visual data of the coffee shop in the form of contact type of image art was mostly found in the form of demand; the gaze or gaze contact component is mostly found in the form of direct or direct; the components of the social distance aspect that are most commonly found are intimate; The most common component of the point of view is the frontal angle. From the aspect of modality, it was found that there were more high modalities than low modalities, both in terms of color saturation, color diversity, color change, contextualization, representation, depth, lighting and brightness